Redox‐Active Guanidines with One or Two Guanidino Groups and Their Integration in Low‐Dimensional Perovskite Structures. Issue 38 (26th September 2019) - Walter, Petra; Kaifer, Elisabeth; Herrmann, Hendrik; Wadepohl, Hubert; Hübner, Olaf; Himmel, Hans‐Jörg
Abstract : Redox‐active guanidines are versatile reagents in redox and proton‐coupled electron‐transfer (PCET) reactions. Recently, they were integrated as sacrificial electron donors for the prohibition of metal oxidation in perovskite materials. Herein we report the synthesis and characterization of several new redox‐active guanidines with aromatic (benzene, naphthalene or anthraquinone) cores. Two of these compounds are then integrated in lead iodide materials. The structure, thermal stability and optical band‐gap of the resulting materials are evaluated. Abstract : Electron‐donor molecules: New redox‐active guanidines were synthesized, their redox properties were evaluated, and two compounds were integrated in low‐dimensional perovskite materials.